2020
DOI: 10.1136/bmjgh-2020-003621
|View full text |Cite
|
Sign up to set email alerts
|

Cash transfers and child nutritional outcomes: a systematic review and meta-analysis

Abstract: BackgroundCash transfer (CT) programmes are implemented widely to alleviate poverty and provide safety nets to vulnerable households with children. However, evidence on the effects of CTs on child health and nutrition outcomes has been mixed. We systematically reviewed evidence of the impact of CTs on child nutritional status and selected proximate determinants.MethodsWe searched articles published between January 1997 and September 2018 using Agris, Econlit, Eldis, IBSS, IDEAS, IFPRI, Google Scholar, PubMed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 13 publications
2
45
0
1
Order By: Relevance
“…A recent meta-analysis of cash transfers (including cash transfers both with and without Nutrition BCC) found very small, but statistically significant improvements on stunting height-for-age z-scores (0.03+/−0.03 SD) compared to a no-intervention control, which accounts for a 2.1% reduction in stunting prevalence [ 4 ]. Among studies delivering Cash + Nutrition BCC, there was a statistically significant 3.1% reduction in stunting prevalence compared to a no-intervention control, but no impact on height-for-age z-score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis of cash transfers (including cash transfers both with and without Nutrition BCC) found very small, but statistically significant improvements on stunting height-for-age z-scores (0.03+/−0.03 SD) compared to a no-intervention control, which accounts for a 2.1% reduction in stunting prevalence [ 4 ]. Among studies delivering Cash + Nutrition BCC, there was a statistically significant 3.1% reduction in stunting prevalence compared to a no-intervention control, but no impact on height-for-age z-score.…”
Section: Discussionmentioning
confidence: 99%
“…Cash transfers alone have had limited impact on distal outcomes for child well-being (e.g., on nutritional status and health [ 4 , 5 ]), despite strong evidence that cash transfers can improve more proximal outcomes, such as improving access to food [ 3 , 13 , 14 ]. Thus, cash-plus programmes were developed in hopes of achieving improvements in these distal, “third-order” outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic review and meta-analysis of 74 studies found that children from households who received cash transfers had reduced stunting by 2.5% and improved consumption of animal foods by 4.5% [44].…”
Section: Discussionmentioning
confidence: 99%
“…With the COVID pandemic still on the rise in many countries, these numbers are expected to worsen considerably in the future. An estimated 90-117 million children are likely to fall into poverty with severe consequences to their health, nutrition status, and possibly also their survival ( Fore, 2020 ; Manley et al, 2020 ). According to a modeling study carried out by Osendarp et al, in a “moderate” scenario, pandemic-related disruptions of the food and health system could result in an additional 9.3 million wasted children and 2.6 million stunted children by 2022 ( Osendarp et al, 2021 )…”
Section: Nutrient Deficiencies As a Global Public Health Problemmentioning
confidence: 99%